Prediction of 20 Meter Sprint Speed via Muscle Fibers and Leg Power at Cibubur National Training Center - Iwan Hermawan; Juriana Juriana; Rina Ambar Dewanti; Fachri Husaini; Najwa Nur Samawati Ali; Vanesha Vanesha; Gatot Jariono (Universitas Negeri Semarang, 2026)
Objective: This study aims to predict the speed of a 20-meter sprint based on the characteristics of muscle fibers and leg power in athletes who participate in a coaching program at the Cibubur National Sports Training Center (CNSTC). This study is expected to provide an understanding of the contribution of physiological factors and explosive abilities of the legs to short-distance sprint performance. Methods: The study used a quantitative approach with a predictive correlational design. The subjects of the study are athletes who undergo a training program at CNSTC Cibubur. The characteristics of the muscle fibers were identified through neuromuscular measurements, while the strength of the limbs was measured using the vertical jump test. Sprint speed is measured through a 20-meter sprint test with an electronic timekeeping device. Data were analyzed using descriptive statistics, correlation tests, and regression analysis to determine the contribution of predictive variables to sprint performance. Results: The results of the analysis showed that the dominance of fast muscle fibers and high leg power were positively and significantly related to the 20-meter sprint speed. Athletes with these characteristics tend to record faster sprint times. Regression analysis also showed that both variables simultaneously made a significant contribution to predicting short-distance sprint performance. Conclusion: Muscle fibers and leg power are important predictors in determining the speed of a 20-meter sprint in athletes, so the development of explosive and neuromuscular exercises has the potential to improve sprint performance more effectively.